A retrospective analysis of patient-specific factors on voriconazole clearance. Issue 1 (December 2016) - Dote, Satoshi; Sawai, Maki; Nozaki, Ayumu; Naruhashi, Kazumasa; Kobayashi, Yuka; Nakanishi, Hirokazu
Abstract Background Voriconazole concentrations display a large variability, which cannot completely be explained by known factors. We investigated the relationships of voriconazole concentration with patient-specific variables and concomitant medication to identify clinical factors affecting voriconazole clearance. Methods A retrospective chart review of voriconazole trough concentration, laboratory data, and concomitant medication in patients was performed. The concentration/dose ratio (C/D-ratio) was assessed as a surrogate marker of total clearance by dividing voriconazole concentration by daily dose per kg of body weight. Results A total of 77 samples from 63 patients were obtained. In multiple linear regression analysis, increased C-reactive protein (CRP) level (p < 0.05) and decreased albumin (Alb) level (p < 0.05) were associated with significantly increased C/D-ratio of voriconazole, and coadministration with a glucocorticoid was associated with significantly (p < 0.05) decreased C/D-ratio of voriconazole (adjustedr 2 = 0.31). Regarding CRP and Alb, receiver operating characteristic curve analysis indicated that increased CRP level and decreased Alb level were significant predictors of toxic trough concentration of voriconazole. For CRP, area under the curve (AUC) and cutoff value were 0.71 (95 % confidence interval (CI), 0.57–0.86, p < 0.01) and 4.7 mg/dl, respectively. For Alb, AUC and cutoff value were 0.68 (95 % CI, 0.53–0.82, p < 0.05) and 2.7 g/dl, respectively. A significant difference was seen in voriconazole trough concentration between patients with hepatotoxicity and those without (5.69 μg/ml vs 3.0 μg/ml, p < 0.001). Conclusion Coadministration of glucocorticoid and inflammation, reflected by elevated CRP level and hypoalbuminemia, are associated with voriconazole clearance. We propose that early measurement of voriconazole concentration before the plateau phase will lead to avoidance of a toxic voriconazole level in patients with elevated CRP level and hypoalbuminemia, although further studies are needed to confirm our findings.